Transforming Derelict Spaces in Tenali into Green Urban Landscapes: A Strategy for Sustainable Urban Regeneration - T. JHANSI,; K. SUNITHA RANI,; T. SWAPNA, (The Bioscan, 2025)
This thesis explores the transformation of derelict spaces in Tenali into green urban landscapes as a strategy for sustainable urban regeneration. With rapid urbanization and the decline of industrial and unused spaces, Tenali has several derelict areas that contribute to urban decay, environmental degradation, and a lack of community engagement. This study aims to identify these underutilized areas and propose their redevelopment into Green Urban landscapes, such as parks, community gardens, and recreational zones, to enhance the city's ecological footprint, social cohesion, and urban aesthetics. The research will involve a comprehensive analysis of existing derelict sites, green space design principles, community involvement strategies, and sustainable urban design approaches, ultimately providing a framework for transforming these spaces into vibrant, multi-functional urban landscapes.